Hubungan Edukasi Leaflet Terhadap Pemahaman Mahasiswa Semarang Tentang Vaksin PCV Pada Pencegahan Risiko Pneumonia - Sarah, Hardianti; Putriningsih, Riamanda; Arifin, Sri Dinda; Mentari, Linda (Lembaga Publikasi Ilmiah Nusantara, 2024)
Pneumonia is a lung infection that can be prevented with vaccines, reducing the risk of death, including among young children. This study aims to assess the effectiveness of leaflets in improving understanding and educating students in Semarang about the PCV (Pneumococcal Conjugate Vaccine) as a preventive measure against pneumonia. The research employs a quantitative descriptive design. A total of 90 respondents, who were active students from the 2017-2018 academic year and willing to participate, were involved in the study. Knowledge was measured using a validated the questionnaire. Educational efforts were carried out by distributing leaflets containing information about PCV vaccination.